2008
DOI: 10.3189/172756408784700707
|View full text |Cite
|
Sign up to set email alerts
|

Snow avalanche mass-balance calculation and simulation-model verification

Abstract: Two-or three-dimensional avalanche-simulation models offer a wide range of applications; however, a challenging model-verification process is demanded, accompanied by a reliable determination of model-input parameters. We show that a verification process can be arranged with remotemonitoring data from an artificially triggered avalanche, leading to the calculation of avalanche mass balance. Two numerical methods are applied to increase the quality of the parameter fit and to reduce the number of simulations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…This is not valid for modeling small-scale avalanches in forested terrain: previous simulations of our data set with RAMMS with alternating ξ values for forested areas (100-1000 m s −2 ) showed that runout distances of 31 out of the 40 avalanches were still overestimated when applying the smallest chosen ξ value of 100 m s −2 (Teich et al, 2012b). Moreover, simulating small-scale avalanches with a model based on Voellmy-type frictional relationships only is generally questionable (Sailer et al, 2008), since the avalanche will not stop as long as the slope angle is larger than the friction angle, i.e., tan φ > µ. Therefore, including physical processes within the avalanche flow such as snow entrainment (mass uptake) and detrainment (mass extraction) is important, for example, modeling the mass removal by trees, remnant stumps or dead wood, as realized in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is not valid for modeling small-scale avalanches in forested terrain: previous simulations of our data set with RAMMS with alternating ξ values for forested areas (100-1000 m s −2 ) showed that runout distances of 31 out of the 40 avalanches were still overestimated when applying the smallest chosen ξ value of 100 m s −2 (Teich et al, 2012b). Moreover, simulating small-scale avalanches with a model based on Voellmy-type frictional relationships only is generally questionable (Sailer et al, 2008), since the avalanche will not stop as long as the slope angle is larger than the friction angle, i.e., tan φ > µ. Therefore, including physical processes within the avalanche flow such as snow entrainment (mass uptake) and detrainment (mass extraction) is important, for example, modeling the mass removal by trees, remnant stumps or dead wood, as realized in this study.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, new surveying techniques like photogrammetry and laser scanning have allowed studying the mass balance of large snow avalanches as well (Vallet et al 2001;Sailer et al 2008;Sovilla et al 2010). However, there are significant sources of error: (i) These measurements determine only the net change of surface elevation, but not the separate snow-depth changes due to erosion and deposition at the same location.…”
Section: Steps Towards Practical Applicationsmentioning
confidence: 99%
“…However, there are significant sources of error: (i) These measurements determine only the net change of surface elevation, but not the separate snow-depth changes due to erosion and deposition at the same location. (ii) The snow depth measurements need to be complemented by manual measurements of the densities of the undisturbed snow pack, the deposits and the remaining snow cover (substrate) underneath the deposit at sufficiently many locations (Issler et al 1996;Sailer et al 2008;Issler et al 2008).…”
Section: Steps Towards Practical Applicationsmentioning
confidence: 99%
“…In past years, a number of avalanche runout modelling studies are performed with statistical models such as alpha-beta (α-β) and runout ratio models (Sinickas and Jamieson 2014), dynamic models such as Voellmy-Salm model (Salm 1993), Voellmy-fluid model (Bartelt, Salm, and Gruber 1999), two-parameter model (Perla, Cheng, and McClung 1980), particle model (Perla 1984), leading edge model (McClung and Mears 1995), AVAL-1D (Oller et al 2010), erosion and deposition model (Naaim, Faung, and Naaim-Bouvet 2003), Snow Avalanche MOdelling and Simulation (SAMOS) model (Sailer, Rammer, and Sample 2002), the modified version of SAMOS, that is, SamosAT (Sailer et al 2008) and rapid mass movement simulation (Christen, Kowalski, and Bartlet 2010). Extensive research has been performed on the identification and probabilistic assessment of weather and snow cover conditions influencing avalanche activity (Hendrikx et al 2005;McClung and Schaerer 2006;Jomelli et al 2007;Schweizer, Mitterer, and Stoffel 2009).…”
Section: Introductionmentioning
confidence: 99%